Analysis of Marketing Strategy of Muslim Street Vendors at Day Night in Efforts to Improve Community Economy in Binjai City - Zunaida Riska Dalimunthe (Budapest International Research and Critics University, 2021)
The obstacles faced by Muslim street vendors at night in an effort to improve the economy of the people in Binjai City, among others evictions occur, considering that evicted street vendors are usually without compensation because they are considered illegal. Some of the obstacles faced by street vendors in Binjai City include the weather that is easy to change like rain, the need to find a bright location, at least have personal lights, and often thuggery comes at night. As well as people who think that the existence of street vendors in urban areas can be said to be irregular, in general they are not orderly and dirty because they sell on sidewalks, in city parks, even on roads, so that they become or cause traffic jams or damage the beauty of the city. The solution made by Muslim street vendors at night in an effort to improve the community's economy in Binjai City Street vendors in Binjai City from the results of the SWOT analysis found that street vendors are in the growth quadrant with a total score of internal business strength having a number of 3.39 and a total power score the industrial attractiveness is 3.34 where the quadrant shows a very favorable situation. Traders have opportunities and strengths so they can take advantage of the opportunities that exist.